How Payment Features Build Consumer Loyalty the Mediating Role of Satisfaction Among Grab Users in Garut, Indonesia - Sopyan ismail; Rahyuniati Setiawan; Eti Kusmiati (Manunggal Halim Jaya, 2026)
This study examines whether consumer satisfaction transmits the influence of payment features to consumer loyalty among Grab users in Garut Regency, Indonesia. A quantitative explanatory survey was conducted with 132 eligible users selected through purposive sampling. The final measurement model contained 22 reflective indicators after five indicators with inadequate loadings were removed. Data were analysed with partial least squares structural equation modelling (PLS-SEM) in SmartPLS 4 using 5,000 bootstrap subsamples. Payment features had a positive and significant effect on consumer satisfaction (β = 0.657, t = 9.716, p < 0.001), and consumer satisfaction had a positive and significant effect on consumer loyalty (β = 0.819, t = 11.242, p < 0.001). The direct effect of payment features on loyalty was positive but not significant (β = 0.102, t = 1.197, p = 0.232), whereas the indirect effect through satisfaction was significant (β = 0.538, t = 7.661, p < 0.001). The pattern therefore supports indirect-only mediation, often described as full mediation. The model explained 43.2% of the variance in satisfaction and 79.1% of the variance in loyalty. Recalculation confirmed the reported AVE values but identified a discriminant-validity concern between satisfaction and loyalty because their correlation (0.886) exceeded both square roots of AVE (0.864 and 0.815). Accordingly, the strong satisfaction–loyalty path should be interpreted cautiously. The findings indicate that payment convenience, security, and usefulness are more likely to build loyalty when they first generate a satisfying transaction experience. Ride-hailing providers should therefore connect payment-feature improvements with service reliability, transparent problem resolution, and consistent user support.